2020
DOI: 10.1038/s41598-020-57915-w
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Measures of Functional Connectivity via Feature Extraction

Abstract: Functional magnetic resonance imaging (fMRI)-based functional connectivity (FC) commonly characterizes the functional connections in the brain. Conventional quantification of FC by Pearson's correlation captures linear, time-domain dependencies among blood-oxygen-level-dependent (BOLD) signals. We examined measures to quantify FC by investigating: (i) Is Pearson's correlation sufficient to characterize FC? (ii) Can alternative measures better quantify FC? (iii) What are the implications of using alternative FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 45 publications
(50 reference statements)
2
74
0
Order By: Relevance
“…However, this does not indicate WM FC is never able to reflect the change in early stages. First, Pearson's correlation coefficient is the most commonly used metric to measure the FC among GM regions, but its accuracy has been proven to be limited [68]. Given the lower SNR in WM BOLD signals compared to GM signals and the difference in hemodynamic response function between WM and GM [20,69], the Pearson's correlation coefficient appears to be even less accurate to represent WM-GM FC.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not indicate WM FC is never able to reflect the change in early stages. First, Pearson's correlation coefficient is the most commonly used metric to measure the FC among GM regions, but its accuracy has been proven to be limited [68]. Given the lower SNR in WM BOLD signals compared to GM signals and the difference in hemodynamic response function between WM and GM [20,69], the Pearson's correlation coefficient appears to be even less accurate to represent WM-GM FC.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the (zero lag) correlation is almost zero. This speaks to the potential importance of using cross-covariance functions (or complex cross spectral in frequency space), when characterizing functional connectivity in distributed brain responses (K. J. Friston, Bastos, et al, 2014 ; Mohanty, Sethares, Nair, & Prabhakaran, 2020 ). This brief treatment of extrinsic coupling has made much of the complex nature of dynamical coupling and how it manifests in terms of functional connectivity.…”
Section: Extrinsic Dynamicsmentioning
confidence: 99%
“…Also, 7 of 9 classifiers gave higher accuracy results for DTW-ΔHb dataset than for CC-ΔHbO dataset. Compared to CC, DTW is a novel measure in functional connectivity estimation and few studies were performed by utilizing DTW for EEG (Karamzadeh et al, 2013), fMRI (Jin et al, 2020; Linke et al, 2020; Meszlenyi, Hermann, et al, 2017; Mohanty et al, 2020) and fNIRS (Gokcay et al, 2019). In a recent study, it was shown that its efficiency outperformed conventional CC approach to detect atypical connectivity patterns in autism and it was reported that DTW was found sensitive to BOLD signal amplitude which is dependent on Hb concentration (Linke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Also, while estimating the connectivity matrices we utilized the conventional Pearson’s correlation coefficient (CC) and Dynamic Time Warping (DTW) distance. DTW is an elastic matching algorithm that allows to capture the lags between two time series and has recently been used as a functional connectivity metric in several neuroimaging studies (Gokcay et al, 2019; Jin et al, 2020; Linke et al, 2020; Meszlényi et al, 2016; Meszlenyi, Buza, et al, 2017; Meszlenyi, Hermann, et al, 2017; Mohanty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%